Membrane Biofouling Control by Surface Modification of Quaternary Ammonium Compound Using Atom-Transfer Radical-Polymerization Method with Silica Nanoparticle as Interlayer - Lehui Ren; Meng Ping; Xingran Zhang (Membranes, 2020)
A facile approach to fabricate antibiofouling membrane was developed by grafting quaternary ammonium compounds (QACs) onto polyvinylidene fluoride (PVDF) membrane via surface-initiated activators regenerated by electron transfer atom-transfer radical-polymerization (ARGET ATRP) method. During the modification process, a hydrophilic silica nanoparticle layer was also immobilized onto the membrane surface as an interlayer through silicification reaction for QAC grafting, which imparted the membrane with favorable surface properties (e.g., hydrophilic and negatively charged surface). The QAC-modified membrane (MQ) showed significantly improved hydrophilicity and permeability mainly due to the introduction of silica nanoparticles and exposure of hydrophilic quaternary ammonium groups instead of long alkyl chains. Furthermore, the coverage of QAC onto membrane surface enabled MQ membrane to have clear antibacterial effect, with an inhibition rate ~99.9% of Escherichia coli (Gram-negative) and Staphylococcus aureus (Gram-positive), respectively. According to the batch filtration test, MQ had better antibiofouling performance compared to the control membrane, which was ascribed to enhanced hydrophilicity and antibacterial activity. Furthermore, the MQ membrane also exhibited impressive stability of QAC upon suffering repeated fouling–cleaning tests. The modification protocols provide a new robust way to fabricate high-performance antibiofouling QAC-based membranes for wastewater treatment.